One-pot formal [3+3] cycloaddition of isocyanoacetates with in situ-derived azoalkenes for the synthesis of 1, 4-dihydropyrimidine derivatives. (21st May 2021) - Liu, Qiang; Chen, Jia-Hui; Yao, Min; Zhao, Zhuo-Yu; Liu, Xiang-Yi; Zhao, Xiao-Li; Shi, Min; Zhao, Mei-Xin
Abstract: The first conjugate addition of α-isocyanoacetates with in situ generated azoalkenes from α-halogeno hydrazones in the presence of Cs2 CO3 has been developed. The reaction condition was suitable to various α-aryl substituted isocyanoacetates as well as aryl and alkyl-substituted α-halogeno hydrazones, affording the corresponding products in good to high yields. The adducts can be easily transformed into biologically attractive 1, 4-dihydropyrimidine derivatives via an intramolecular cyclization by treating with AgOAc. The one-pot conjugate addition/intramolecular cyclization has also been investigated to furnish the formal [3 + 3] cycloadduct, 1, 4-dihydropyrimidine derivatives. Graphical abstract: Image 1